2013
DOI: 10.1179/1743294412y.0000000102
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bath temperature on zinc plating and passivation process

Abstract: Zinc films were prepared by a typical chloride zinc system electrodeposition on iron substrate. Effects of different temperatures on deposition rate, structures and surface morphology of zinc films were investigated in the paper. Trivalent chromium passivation technology was also studied in the paper to improve corrosion resistance of zinc films. Higher temperature could dramatically improve bath conductivity, which contributed directly to the rise in mass transfer and deposition rate. The deposited films were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…There is a great demand for the development of trivalent chromium passivation technology for zinc coating with the development of environmental protection. However, the component of trivalent chromium passivation solution is more complex and less stable compared to hexavalent chromium passivation solution [18]. Cr +3 passivation baths are organic (resin), or inorganic (silicate) based.…”
Section: Introductionmentioning
confidence: 99%
“…There is a great demand for the development of trivalent chromium passivation technology for zinc coating with the development of environmental protection. However, the component of trivalent chromium passivation solution is more complex and less stable compared to hexavalent chromium passivation solution [18]. Cr +3 passivation baths are organic (resin), or inorganic (silicate) based.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study on electrodeposited zinc is very limited and has been largely focused on the acid bath and the effects of organic additives [ 16 , 17 , 18 , 19 , 20 ]. Among various process parameters, plating temperature, pH of plating baths, and current density are found to influence the morphology and corrosion behavior of zinc deposits [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In industry, the deposition of Zn coatings usually relies upon the electrodeposition techniques due to the high efficiency, low cost and easy preparation of nanoparticulate films. Many factors have been reported that affect the surface morphology and texture of the electrodeposited Zn films, such as the temperature, pH value, current density, [3][4][5] concentrations of Zn(II) ions, 6 usage of agents 7 and properties of anions 8,9 because electrodeposition generally involves the following processes: liquid phase mass transfer, pretransformation, charge transfer and electrocrystallisation. It is well known that the organic additives also play very important roles in the electrolytic baths, 10,11 which improve throwing power and solubility of the brighteners in the bath solutions, and thus smoothen and refine the grain size of deposited films.…”
Section: Introductionmentioning
confidence: 99%